Linguistic features of literary theme: some halliday-type principles applied to 'surfacing' (margareth atwood 1972) - M. Nélia Scott (Ilha do Desterro)
Halliday divides the functions of language into three 'macro-functions' which he calls: Ideational function, expressing content, or the propositional content of the speaker's experiences of the real and inner world; Interpersonal function, which is the means whereby we achieve communication, taking on speech roles viz-a-viz other people,00mplaining, narrating, enquiring, encouraging, etc.; and Textual function, which serves to connect discourse, weaving it together. Under this latter function comes the notion of cohesion. Phoric' elements are parts of the reference system needed for a text to be cohesive. We elucidate and refer to 'phoric' elements in more detail below. It is important to note that all these three macro-functions are present at the same time in a text. Halliday describes the choice of (sets of different) options the speaker makes in the language system, to express his experiences. 'All options are embedded in the language system: the system is a network of options, deriving from all the various functions of language' (1973:111) Thus a certain choice of (one set of different) options rather than another can be said to have been motivated by what the speaker (or writer) wanted to mean -- to convey or emphasize. Prominence of certain features in a text, then, stands out in a particular Way, suggesting or pressing the reader to take notice of it, this recognition contributing towards a more complete understanding of the writer's work. This is Halliday's intention in his study of The Inheritors (Halliday 1973:103-43).